Café: emoções, hábitos, preferências, aspectos sensoriais e extrínsecos - Cardoso, Ana Beatriz Dos Anjos (2021)
Coffee has a very meaningful contribution to Brazil. The country is the world’s largest producer and exporter, this being the fifth product on the list of Brazilian exports. Brazilian consumers are increasingly looking for products with higher quality and differentiated attributes. Knowing the habits of consumers is of great importance for producers, roasters, cooperatives, and coffee shops. In this sense, we sought to investigate the sensory profile of the Brazilian coffee consumer before and during the COVID-19 pandemic; why the habit of drinking coffee started; types of coffee most consumed; ways of preparing the drink, brands, and preferred times of consumption. The influence of extrinsic aspects such as packaging and price on the product purchase decision process was also evaluated. Also, the CATA list proposed by Richardi (2016) will be analy zed. Two main searches will be done. The first was carried out online, via Google Forms. All analyzes will use RStudio software version 4.0.4 and the programming language R. Exploratory analyzes will be carried out using descriptive statistics, Chi-square test, Fisher’s exact tests, McNemar tests, correspondence analysis, principal component analysis, and factor analysis. It was found in this work a prevalence of females with an average age of 35 years, frequency of consumption, mostly twice a day, the main reason for the beginning of the habit of drinking coffee is the family tradition and the preferred brand to Pilão. The main way to drink coffee is pure, with white sugar and early in the morning. The worst time for consumption, disregarding the night and dawn is just before lunch. Brazilian consumers prefer traditional and extra-strong coffees. Changes in the pattern of consumption during the pandemic were observed. The most affected variable was the place of consumption, followed by the number of cups and times of consumption. In addition, there was a change in the pattern of consumption of strained coffee and soluble coffee, with a decrease in both. The study also selected a lexicon of emotions evoked by coffee from the CATA methodology with 22 emotional terms.